Where our food comes from retracing Nikolay Vavilov's quest to end famine - Nabhan, Gary Paul. (Washington, DC : Island Press/Shearwater Books, 2009)
The future of our food depends on seeds in orchards and fields the world over. In 1943, one of the first to recognize this fact, botanist Nikolay Vavilov, lay dying of starvation in a Soviet prison. But in the years before Stalin jailed him as a scapegoat, Vavilov had traveled over five continents, collecting hundreds of thousands of seeds in an effort to outline the ancient centers of agricultural diversity and guard against widespread hunger. Now, another remarkable scientist--and vivid storyteller--has retraced his footsteps. Here, Gary Paul Nabhan weaves together Vavilov's extraordinary story with his own expeditions to Earth's richest agricultural landscapes and the cultures that tend them. In his travels, Nabhan shows how climate change, free trade policies, genetic engineering, and loss of traditional knowledge are threatening our food supply. But he also shows what resilient farmers and scientists in many regions are doing to save the remaining living riches of our world.--From publisher description.
The art museum and the seed bank -- The hunger artist and the horn of plenty -- Melting glaciers and waves of grain: the Pamirs -- Drought and the decline of variety: the Po Valley -- From breadbasket to basket case: the Levant -- Date palm oases and desert crops: the Maghreb -- Finding food in famine's wake: Ethiopia -- Apples and boomtown growth: Kazakhstan -- Rediscovering America and surviving the Dust Bowl: the U.S. Southwest -- Logged forests and lost seeds: the Sierra Madre -- Deep into the tropical forests of the Amazon -- The last expedition.
Includes bibliographical references (p. 199-210) and index.
Keywords: Vavilov, N. I. -- 1887-1943.; Centers of plant diversity; Plant collecting; Botanical specimens -- Collection and preservation; Food crops -- Germplasm resources -- Collection and preservation; Electronic books